2004
DOI: 10.1093/jac/dkh358
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of AVE1330A, an innovative broad-spectrum non- -lactam  -lactamase inhibitor

Abstract: The combination of ceftazidime with AVE1330A exhibited broad-spectrum activity against Ambler class A- and class C-producing Enterobacteriaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(121 citation statements)
references
References 19 publications
3
117
0
1
Order By: Relevance
“…The measured off-rate for avibactam suggested that slow deacylation through hydrolysis or reversibility was occurring, and it is in contrast to previously reported extremely long t 1/2 values of >1 or >7 d for avibactam inhibition of TEM-1 (15,16). We investigated the methods used in these earlier studies and concluded that these data resulted from measuring initial rates of enzyme activity within seconds after dilution of a 1 μM acylenzyme (EI*) complex.…”
Section: Resultsmentioning
confidence: 93%
“…The measured off-rate for avibactam suggested that slow deacylation through hydrolysis or reversibility was occurring, and it is in contrast to previously reported extremely long t 1/2 values of >1 or >7 d for avibactam inhibition of TEM-1 (15,16). We investigated the methods used in these earlier studies and concluded that these data resulted from measuring initial rates of enzyme activity within seconds after dilution of a 1 μM acylenzyme (EI*) complex.…”
Section: Resultsmentioning
confidence: 93%
“…A remarkable property of NXL104 is the prolonged deacylation rate. The 50% enzyme recovery time point was 7 days for both TEM-1 and P99 (compared to 7 min for TEM-1 and clavulanate and 290 min for P99 and tazobactam), suggesting the presence of a very stable and long-lived intermediate species (31). The formation of a covalent complex has been supported by an ESI-MS study of TEM-1 and NXL104 (391).…”
Section: Non-␤-lactam Inhibitorsmentioning
confidence: 85%
“…1, compound 26) is a bridged diazabicyclo[3.2.1]octanone non-␤-lactam inhibitor with very promising activity against class A, C, and D ␤-lactamases (31,116,240,390). The majority of the published work on NXL104 describes MIC testing, although IC 50 s of 8, 38, and 80 nM have been reported for class A TEM-1 and KPC-2 and class C P99 enzymes, respectively (31,390). A remarkable property of NXL104 is the prolonged deacylation rate.…”
Section: Non-␤-lactam Inhibitorsmentioning
confidence: 99%
“…It displays a broad spectrum of inhibitory activity against both class A and class C ␤-lactamases, including Klebsiella pneumoniae carbapenemase (KPC) enzymes (2), the AmpC ␤-lactamase of Pseudomonas aeruginosa (3), and extendedspectrum ␤-lactamases such as TEM, SHV, and CTX-M variants (4,5). In studies with isolated enzymes, avibactam inactivates ␤-lactamases at low 50% inhibitory concentrations and with low turnover numbers (6,7).…”
mentioning
confidence: 99%
“…It also inhibits some class D ␤-lactamases, OXA-48, for example (8). Avibactam has little intrinsic antibacterial activity but efficiently protects ␤-lactams from ␤-lactamase-catalyzed hydrolysis in a range of members of the family Enterobacteriaceae and in P. aeruginosa (3)(4)(5)9). That a combination of ceftazidime and avibactam protects against bacterial infections by ␤-lactamase-producing bacteria has been demonstrated in animal models (10,11), and two successful phase 2 human studies have been reported (12,13).…”
mentioning
confidence: 99%